Compound leaf development in model plant species. (February 2015) - Bar, Maya; Ori, Naomi
Highlights: Variability of compound-leaf forms is generated by flexible tuning of partially common factors. Prolonged morphogenesis is essential for compound leaf development. Cardamine, pea, medicago and tomato serve as model plants in the research of compound leaf development. Compound leaf patterning involves flexible interactions between transcription factors and hormones. Abstract : Plant leaves develop in accordance with a common basic program, which is flexibly adjusted to the species, developmental stage and environment. Two key stages of leaf development are morphogenesis and differentiation. In the case of compound leaves, the morphogenesis stage is prolonged as compared to simple leaves, allowing for the initiation of leaflets. Here, we review recent advances in the understanding of how plant hormones and transcriptional regulators modulate compound leaf development, yielding a substantial diversity of leaf forms, focusing on four model compound leaf organisms: cardamine ( Cardamine hirsuta ), tomato ( Solanum lycopersicum ), medicago ( Medicago truncatula ) and pea ( Pisum sativum ).